How natural resources shape the industrial development: Evidence from N-10 countries - Chairul, Reza Pahlevi; Falianty, Telisa Aulia; Triaswati, Ninasapti; Revindo, Mohamad Dian (Universitas Muhammadiyah Yogyakarta, 2025)
This study analyzes the effect of natural resources on the manufacturing industry. It aims to fill the gap in the research on the impact of natural resources on industrial productivity since there is very limited literature on such a topic, particularly in the Next Eleven countries (N-11), excluding South Korea (referred to as the N-10 countries). South Korea is not included as a sample because it does not have many natural resources. The N-10 countries (Vietnam, Turkey, Philippines, Pakistan, Nigeria, Mexico, Iran, Indonesia, Egypt, and Bangladesh) have a large population, rapid economic growth, and political and economic stability. The Generalized Method of Moments (GMM) is implemented using data panels of the N-10 countries with natural resources from 2015 to 2021. This study confirms that the resource curse exists, as evidenced by the detrimental effects of abundant natural resources on industrial productivity. Empirical findings have also documented a significantly adverse impact of corruption practices in the manufacturing sector. Meanwhile, capital and trade openness should be further improved to encourage value-added industries. Based on the results of this study, the N-10 countries are recommended to diversify their economies, reduce reliance on natural resources, and strengthen the control of corruption.